2017
DOI: 10.1007/s00253-017-8391-5
|View full text |Cite
|
Sign up to set email alerts
|

Illumina sequencing of bacterial 16S rDNA and 16S rRNA reveals seasonal and species-specific variation in bacterial communities in four moss species

Abstract: In order to better understand the factors that influence bacterial diversity and community composition in moss-associated bacteria, a study of bacterial communities in four moss species collected in three seasons was carried out via high-throughput sequencing of 16S rDNA and 16S rRNA. Moss species included Cratoneuron filicinum, Pylaisiella polyantha, Campyliadelphus polygamum, and Grimmia pilifera, with samples collected in May, July, and October 2015 from rocks at Beijing Songshan National Nature Reserve. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Taxonomic analysis revealed that Actinobacteria and Proteobacteria were most abundant across all samples at the phylum level, with relatively stable proportions of 19.54-45.83% and 19.21-31.20%, respectively, which are similar to some previous studies on bryophytes collected from different areas (Ma et al 2017;Tang et al 2016). Additionally, Cyanobacteria, Chloroflexi, Acidobacteria, Bacteroidetes, and Verrucomicrobia were the dominant phyla from the whole areas of two moss species according to relative abundance (> 1% was identified as a dominant bacterium) (Supplemental Fig.…”
Section: Moss Microbiomessupporting
confidence: 86%
See 1 more Smart Citation
“…Taxonomic analysis revealed that Actinobacteria and Proteobacteria were most abundant across all samples at the phylum level, with relatively stable proportions of 19.54-45.83% and 19.21-31.20%, respectively, which are similar to some previous studies on bryophytes collected from different areas (Ma et al 2017;Tang et al 2016). Additionally, Cyanobacteria, Chloroflexi, Acidobacteria, Bacteroidetes, and Verrucomicrobia were the dominant phyla from the whole areas of two moss species according to relative abundance (> 1% was identified as a dominant bacterium) (Supplemental Fig.…”
Section: Moss Microbiomessupporting
confidence: 86%
“…Nevertheless, exploration of the diversity and community of non-lichenized fungi with bryophytes is still quite limited (Bates et al 2012;Zhang et al 2016;Liu et al 2017). Most of these studies focused on the diversity of mossrelated bacterial communities in deserts, forests, grasslands, and alpine regions, while the structure and function of bryophyte-symbiotic microbial communities in karst rocky desertification habitats have not been reported (Opelt et al 2007;Tang et al 2016;Ma et al 2017). Studies have shown that Proteobacteria and Actinobacteria were the two most abundant phyla associated with mosses under different habitats, and large amounts of unclassified bacteria could interact with the moss.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, for low-quality sequence removal rate, it seems that Ion S5-xl platform showed better than Hiseq 2500 platform. For the microbiota analysis, alpha diversity index is usually used to show the diversity within individual, where Chao1, Shannon, simpson, observed_specise, PD_whole_tree, good_coverage are the general index included [18,19,20].There existed significant statistical difference in the alpha diversity index in this study between the two sequencing platforms (P<0.01), except the Shannon index, which is to evaluate the diversity of the bacterial community. As expected, microbial species sequenced by two platforms are basically the same evaluated by Shannon index [21].…”
Section: Discussionmentioning
confidence: 83%
“…Metatranscriptomic analyses provide insight into current metabolic state of a sample community, but without evidence of enzyme activity or translation (Blazewicz et al ). Combined DNA and RNA analyses lead to more accurate environmental assessments (Dupont et al ; Stecher et al ; Ma et al ).…”
mentioning
confidence: 99%
“…Metatranscriptomic analyses provide insight into current metabolic state of a sample community, but without evidence of enzyme activity or translation (Blazewicz et al 2013). Combined DNA and RNA analyses lead to more accurate environmental assessments (Dupont et al 2015;Stecher et al 2016;Ma et al 2017). The effectiveness of molecular biologic procedures involving RNA mostly depends on the integrity, purity, and quantity of the extracted RNA (Santiago-Vazquez et al 2006;Johnson et al 2012).…”
mentioning
confidence: 99%